Student- and school-level belonging and commitment and student smoking, drinking and misbehaviour. (March 2017) - Bonell, Christopher; Shackleton, Nichola; Fletcher, Adam; Jamal, Farah; Allen, Elizabeth; Mathiot, Anne; Markham, Wolfgang; Aveyard, Paul; Viner, Russell
Objectives: It has been suggested that students are healthier in schools where more students are committed to school. Previous research has examined this only using a proxy measure of value-added education (a measure of whether school-level attendance and attainment are higher than predicted by students' social profile), finding associations with smoking tobacco, use of alcohol and illicit drugs, and violence. These findings do not provide direct insights into the associations between school-level aggregate student commitment and health behaviours, and may simply reflect the proxy measure being residually confounded by unmeasured student characteristics. We examined the previously used proxy measure of value-added education, as well as direct measures at the level of the school and the student of lack of student commitment to school to see whether these were associated with students' self-reported smoking tobacco, alcohol use and school misbehaviour. Design: Cross-sectional survey. Setting: A total of 40 schools in south-east England. Methods: Multi-level analyses. Results: There were associations between school- and student-level measures of lack of commitment to school and tobacco smoking, alcohol use and school misbehaviour outcomes, but the proxy measure of school-level commitment, value-added education, was not associated with these outcomes. A sensitivity analysis focused only on violent aspects of school misbehaviour found a pattern of associations identical to that found for the measure of misbehaviour. Conclusion: Our study provides the first direct evidence in support of the Theory of Human Functioning and School Organisation.